CIFOR's management information system: from concept to implementation - Ibach, M.O. (Center for International Forestry Research, 1999)
This study describes the concept of a management information system (MIS) developed for the Center for International Forestry Research. A definition of MIS and the institutional background are given, followed by a description of the organisational structure, definition of MIS requirements and the procedures and results of an information requirements survey. The core of the study is the design of the MIS which focuses on outputs, inputs, processing, storage and personnel as key elements of the system. Issues related to implementation and maintenance of the proposed system are discussed and key databases described. Emphasis is given to personnel, soft- and hardware requirements, system architecture, training and procedural aspects. The study concludes with a discussion of project management requirements, critical success factors, monitoring and evaluation procedures, and the potential generalisation of the concept.